2009
DOI: 10.1007/s11999-009-0851-5
|View full text |Cite
|
Sign up to set email alerts
|

Bone Stress Injuries Are Common in Female Military Trainees: A Preliminary Study

Abstract: Although bone stress injuries are common in male military trainees, it is not known how common they are in female trainees. It also is unclear whether asymptomatic bone stress injuries heal if intensive training is continued. We prospectively followed 10 female trainees of a military Reserve Officer Course. The subjects underwent clinical and MRI examinations of the pelvis, thighs, and lower legs at the beginning, once during, and at the end of their 3-month course. We identified two to five injuries in every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 30 publications
0
21
0
4
Order By: Relevance
“…Radiographic findings are found 2 to 8 weeks after symptom onset. At this time point the sensitivities of the radiographs can be as low as 10%, which increases up to 70% on follow up [6] . With the potential that stress fractures will take 8 weeks to become evident on radiological imaging this may not be of great diagnostic use [6,7] .…”
Section: R R Lmentioning
confidence: 84%
See 1 more Smart Citation
“…Radiographic findings are found 2 to 8 weeks after symptom onset. At this time point the sensitivities of the radiographs can be as low as 10%, which increases up to 70% on follow up [6] . With the potential that stress fractures will take 8 weeks to become evident on radiological imaging this may not be of great diagnostic use [6,7] .…”
Section: R R Lmentioning
confidence: 84%
“…At this time point the sensitivities of the radiographs can be as low as 10%, which increases up to 70% on follow up [6] . With the potential that stress fractures will take 8 weeks to become evident on radiological imaging this may not be of great diagnostic use [6,7] . Typical findings include a fine area of periosteal bone elevation, sclerosis and an area of low-density bone may also be seen [8] .…”
Section: R R Lmentioning
confidence: 84%
“…This leads to the acceleration of normal bone remodeling, the production of micro-fractures (caused by insufficient time for the bone to repair), the creation of a bone stress injury (i.e., stress reaction), and eventually, a stress fracture. 11,12 Persons who participate in repetitive, high intensity training, such as athletes and military recruits, are at increased risk of developing stress fractures. Stress fractures, classically been described in military recruits and in sports persons, hence, studied and reported extensively in such populations.…”
Section: Discussionmentioning
confidence: 99%
“…Niva et al performed a study and reported of bone stress injuries at femur and tibia which were asymptomatic at military recruits during intensive training and did not recommend routine screening of asymptomatic military trainees [7]. A systematic review by Snyder et al showed evidence of shoe insoles to reduce the overall femoral and tibial stress fracture incidence during military training by improving biomechanics, lessening fatigue, and attenuating impact.…”
Section: Discussionmentioning
confidence: 99%